Pumilio Regulates Sleep Homeostasis in Response to Chronic Sleep Deprivation in Drosophila melanogaster - De Jesús-Olmo, Luis A.; Rodríguez, Norma; Francia, Marcelo; Alemán-Rios, Jonathan; Pacheco-Agosto, Carlos J.; Ortega-Torres, Joselyn; Nieves, Richard; Fuenzalida-Uribe, Nicolás; Ghezzi, Alfredo; Agosto, José L. (Frontiers in Neuroscience, 2020)
Recent studies have identified the Drosophila brain circuits involved in the sleep/wake switch and have pointed to the modulation of neuronal excitability as one of the underlying mechanisms triggering sleep need. In this study we aimed to explore the link between the homeostatic regulation of neuronal excitability and sleep behavior in the circadian circuit. For this purpose, we selected Pumilio (Pum), whose main function is to repress protein translation and has been linked to modulation of neuronal excitability during chronic patterns of altered neuronal activity. Here we explore the effects of Pum on sleep homeostasis in Drosophila melanogaster, which shares most of the major features of mammalian sleep homeostasis. Our evidence indicates that Pum is necessary for sleep rebound and that its effect is more pronounced during chronic sleep deprivation (84 hours) than acute deprivation (12 hours). Knockdown of pum, results in a reduction of sleep rebound during acute sleep deprivation and the complete abolishment of sleep rebound during chronic sleep deprivation. Based on these findings, we propose that Pum is a critical regulator of sleep homeostasis through neural adaptations triggered during sleep deprivation.